Isolation and molecular characterization of circulating tumor cells - Magbanua, Mark Jesus M.; Park, John W. (Springer, 2017)
"Numerous studies have shown that elevated levels of circulating tumor cells (CTCs) in blood of cancer patients are associated with poor response to treatment and inferior survival probabilities. Despite this clinical significance, the molecular biology of CTCs remains poorly understood. The paucity in molecular information can be attributed to the tremendous technical challenges involved in isolating these extremely rare cells. Recent technological advancements in rare-cell technology, however, have allowed for the reliable enrichment and isolation of CTCs. Consequently, the use of recently developed molecular approaches --e.g., multiplexed QPCR, microarray, and next generation sequencing analyses-- to profile CTCs have provided novel insights into the molecular makeup of these tumor cells. This book discusses approaches for enrichment and isolation of CTCs as well as recent advances in comprehensive molecular profiling of CTCs using cutting-edge omics technology"--Publisher's description.
Keywords: Metastasis.; elektronické knihy; electronic books